PENGARUH KEPUASAN KERJA DAN KOMUNIKASI TERHADAP TURNOVER INTENTION PADA DEPARTEMEN QA BAGIAN QC PT. X GARMENT KABUPATEN TASIKMALAYA - Ajat Sudrajat (Jurnal Computech & Bisnis (e-Journal), 2021)
This study aims to determine the effect of satisfaction and communication on turnover intention, partially and simultaneously at PT. X Garment, Tasikmalaya Regency. This study uses an explanatory research method with a quantitative approach. The data analysis method used is descriptive analysis and path analysis. The research population is all employees of the QC section at PT. X Garment as many as 109 respondents. Data collection techniques using questionnaires and data analysis with the help of SPSS 24.0 program. The results of this study indicate that job satisfaction has a positive effect on turnover intention. Communication has a positive effect on turnover intention. Job satisfaction and communication simultaneously affect turnover intention. It can be concluded that high monkey satisfaction and effective communication will reduce high turnover rates.  Keywords: Job Satisfaction, Communication, Turnover Intention.DOI: 10.5281/zenodo.5784133